Combination therapy in severe Acinetobacter baumannii infections: an update on the evidence to date. (June 2014) - Durante-Mangoni, Emanuele; Utili, Riccardo; Zarrilli, Raffaele
ABSTRACT: : Acinetobacter baumannii is a drug-resistant Gram-negative pathogen increasingly causing hospital-acquired infections in critically ill patients. In this review, we summarize the current mechanisms of antimicrobial resistance in A. baumannii and describe in detail recent in vitro and in vivo experimental data on the activity of antimicrobial combinations against this microorganism. We then introduce the rationale for the use of combination antibiotic therapy in resistant A. baumannii infections. Finally, we present and critically discuss both uncontrolled clinical studies and the few randomized clinical trials of combination antimicrobial therapy for these infections, with a special focus on ongoing multinational trials and optimal approach to future research in this field.